Genome sequence of metarhizium rileyi, a microbial control agent for lepidoptera - Binneck, Eliseu (2019)
Metarhizium rileyi (formerly known as Nomuraea rileyi) is a potential agent for microbial control of many insect pests from the order Lepidoptera, the damages of which can cause considerable loss of productivity in agriculture. We report the genome sequence and annotation of M. rileyi strain Cep018-CH2/ARSEF 7053.